2006
DOI: 10.4049/jimmunol.177.4.2536
|View full text |Cite
|
Sign up to set email alerts
|

Local CD11c+ MHC Class II− Precursors Generate Lung Dendritic Cells during Respiratory Viral Infection, but Are Depleted in the Process

Abstract: Increases in numbers of lung dendritic cells (DC) observed during respiratory viral infections are assumed to be due to recruitment from bone marrow precursors. No local production has been demonstrated. In this study, we isolated defined populations of murine lung cells based on CD11c and MHC class II (MHC II) expression. After culture for 12 days with GM-CSF, we analyzed cell numbers, DC surface markers, and Ag-presenting capacity. Only CD11c+ MHC II− cells from naive mice proliferated, yielding myeloid DC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
(32 reference statements)
1
41
1
Order By: Relevance
“…3c). This finding, although similar to what has been reported by at least one other group, contrasts with reports suggesting that lung cDCs were of the myeloid (CD11b ϩ ) phenotype at baseline (22,29,30). With viral inoculation, we found expression of CD11b as well as the costimulatory molecule CD86 and increased expression of MHC-II (Fig.…”
Section: Paramyxoviral Respiratory Infection Alters Lung DC Levelscontrasting
confidence: 57%
See 2 more Smart Citations
“…3c). This finding, although similar to what has been reported by at least one other group, contrasts with reports suggesting that lung cDCs were of the myeloid (CD11b ϩ ) phenotype at baseline (22,29,30). With viral inoculation, we found expression of CD11b as well as the costimulatory molecule CD86 and increased expression of MHC-II (Fig.…”
Section: Paramyxoviral Respiratory Infection Alters Lung DC Levelscontrasting
confidence: 57%
“…Previous work on respiratory viral disease and lung DCs has focused primarily on RSV infection of BALB/c mice (15,16,22,23). In this RSV model, the number of both cDCs and pDCs appear to increase in the airway tissue with viral infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been shown in murine models of respiratory viral infection, potent type I IFN stimulation causes significant loss of CD11c + cells from the lung and appears to have an important role in immunoregulation in the airways (32,33). The WT mice had significantly more TNF-α in their airways than Ifnar -/-mice, and we have previously demonstrated that TNF-α signaling is associated with substantial pulmonary pathology in response to S. aureus (7).…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, it has become evident that BM DC precursors enter the circulation and extravasate into secondary lymphoid organs, skin, and lung where they finally differentiate into DCs. 18,19,21,22,[24][25][26][27][28] In the steady state, spleen and lymph node DCs do not seem to be derived from monocytes but from specialized precursors. 21,29 Regulation of cellular homeostasis in other immune compartments is relatively well defined.…”
mentioning
confidence: 99%